Lattice Boltzmann Simulation of Magnetic Field Effect on Natural Convection of Power-Law Nanofluids in Rectangular Enclosures (Advances in Applied Mathematics and Mechanics, 2018)
In this paper, the magnetic field effects on natural convection of power-lawnanofluids in rectangular enclosures are investigated numerically with the latticeBoltzmann method. The fluid in the cavity is a water-based nanofluid containing Cunanoparticles and the investigations are carried out for different governing parametersincluding Hartmann number (0.0≤$Ha$≤20.0), Rayleigh number (104≤$Ra$≤106),power-law index (0.5≤$n$≤1.0), nanopartical volume fraction (0.0≤$ϕ$≤0.1) and aspectratio (0.125≤$AR$≤8.0). The results reveal that the flow oscillations can be suppressedeffectively by imposing an external magnetic field and the augmentation of Hartmannnumber and power-law index generally decreases the heat transfer rate. Additionally,it is observed that the average Nusselt number is increased with the increase ofRayleigh number and nanoparticle volume fraction. Moreover, the present results alsoindicate that there is a critical value for aspect ratio at which the impact on heat transferis the most pronounced.